Hemodynamics of a right ventricular outflow tract aneurysm assessed with 4D flow MRI before and after unilateral pulmonary artery balloon angioplasty: A case report - Hideharu Oka, MD, PhD; Kouichi Nakau, MD; Keita Ito, MD; Rina Imanishi, MD; Kazunori Fukao, RT; Sadahiro Nakagawa, RT, PhD; Tatsuya Suzuki, RT; Satoru Takahashi, MD, PhD (Radiology Case Reports)
Right ventricular outflow tract aneurysms are rare postoperative complications associated with congenital heart diseases. The hemodynamics associated with a right ventricular outflow tract aneurysm serve as important risk indicators for aneurysm expansion and thrombus formation; however, they have not been thoroughly evaluated. A 3-year-old girl was diagnosed with Double-outlet right ventricle who underwent surgical correction with patch enlargement of the right ventricular outflow tract at 2.5 years. Postoperatively, a patch expansion mass was observed and 4D flow MRI showed vortex flow. Notably, vortex flow within the aneurysm persisted even after balloon dilation of the unilateral pulmonary artery. Evaluating blood flow in right ventricular outflow tract aneurysms is crucial for determining prognosis and guiding treatment strategies.